Identifikasi Senyawa Penyusun Minyak Kulit Batang Kayu Manis (Cinnamomum cassia) Menggunakan GC-MS - Prasetya, Nor Basid Adiwibawa; Ngadiwiyana, Ngadiwiyana (Jurnal Kimia Sains dan Aplikasi, 2006)
The steam-distilled volatile oil of the cinnamon bark (Cinnamomum cassia) has been analysed by gas chromatography – mass spectrophotometer (GC-MS). It was resulted three chromatogram peaks, there were identified as cinnamaldehyde (91.18 %), eugenol (7.64 %) and cinnamyl acetate (1.18 %) respectively.Keywords: Cinnamomum cassia, GC-MS, Cinnamadehyde, eugenol, cinnamyl acetate